Pharmacokinetic, pharmacodynamic and transcriptomic analyses of verubecestat treatment in 5XFAD mice: Development of new models and analysis methods/novel assays and technologies. (7th December 2020) - Territo, Paul R.; Quinney, Sara K.; Biesdorf, Carla; Masters, Andrea R.; Onos, Kristen; Haynes, Leslie; Keezer, Kelly; Cope, Zackery A.; Meyer, Jill A.; Peters, Jonathan; Persohn, Scott C.; Figueiredo, Lucas; et al.
Abstract: Background: The Preclinical Testing Core (PTC) of the Model Organism Development for Late Onset Alzheimer's Disease (MODEL‐AD) consortium established a preclinical strategy with go/no‐go decision points that permits unbiased assessments of potential therapeutic agents. In models at disease‐relevant ages, this strategy includes: 1) drug formulation, stability, and in vivo pharmacokinetics (PK); and 2) pharmacodynamics (PD) readouts of target engagement and disease modifying activity via non‐invasive PET/MRI, behavior, and transcriptomics. As part of the pipeline validation, verubecestat (VER), a BACE1 inhibitor, was selected for testing in 5XFAD mice. Methods: PK analysis was performed in 6 month aged 5XFAD mice of both sexes, for both oral gavage (PO) and drug milled into diet (10‐100 mg/kg) with blood and brain concentrations analyzed via LC/MS. PK/PD modeling determined dosing regimen for chronic treatments started at 3 months. All PD endpoints (n = 10‐15/sex/genotype/treatment) were measured at 6‐7 months of age, and included: 18‐FDG PET/MR, 18F‐AV45 PET/MR, autoradiography, immunohistochemistry, and behavioral assessments. Post treatment gene expression profiling was conducted using the nanoString and aligned to AMP‐AD consensus clusters. Results: Initial PK analysis revealed rapid clearance of VER following PO dosing, thus all PD experiments were performed via chronic exposure to drug formulated in diet (10, 30, and 100 mg/kg/day). Prophylactic treatment with VER produced robust coat color changes consistent with hair color changes reported in the clinic. Moreover, VER resulted in dose‐dependent reductions in amyloid deposition via 18F‐AV45 PET, but did not alter glucose uptake via 18F‐FDG PET. VER failed to improve cognition in 5XFAD mice. Transcriptomics revealed dose depended genes expression that mapped to AMP‐AD consensus clusters for immune response, DNA repair, and RNA metabolism. Conclusions: The effects of VER dosing on PD endpoints revealed the expected results consistent with clinical findings. Moreover, VER failed to improve cognitive behavior in 5XFAD mice, in line with the lack of cognitive improvement in patients. Together these data positive support for pipeline validation of the MODEL‐AD PTC, and highlight the importance for post‐treatment transcriptomics to align model systems with drug mechanism of actions.